Neurologic Complications Caused by Epstein-Barr Virus in Pediatric Patients. (May 2016) - Mazur-Melewska, Katarzyna; Breńska, Iwona; Jończyk-Potoczna, Katarzyna; Kemnitz, Paweł; Pieczonka-Ruszkowska, Ilona; Mania, Anna; Służewski, Wojciech; Figlerowicz, Magdalena
We retrospectively analyzed the medical documentation of 194 children infected with Epstein-Barr virus. The diagnosis was based on clinical symptoms and the presence of the viral capsid antigen IgM antibody. Patients with severe neurologic complications also underwent neurologic examination, magnetic resonance imaging (MRI), and electroencephalography (EEG). There were 2 peaks in incidence of infection; the first one in young children aged 1 to 5 years represented 62.0% of cases. The second peak (24.6% of patients) occurred in teenagers. Febrile seizures were confirmed in 3.1% of affected children younger than 5 years and headaches in 24.2% patients, mostly older children. Ten children presented severe, neurologic complications: meningoencephalitis, acute encephalitis, acute cerebellitis, transverse myelitis, and myeloradiculitis. Our study identified a variety of Epstein-Barr virus–related neurologic complications. Epstein-Barr virus should be routinely tested for when a child presents with an apparent neuroinfection as it is a common pathogen that can induce a wide variety of signs and symptoms.